Comparison of the Performance of CMIP5 and CMIP6 in the Prediction of Rainfall Trends, Case Study Quebec City - Salimi, Amirhossein; Ghobrial, Tadros; Bonakdari, Hossein (ECWS-7 2023, 2023)

Assessment of the Potential Hydrological Impacts of Climate Change in Quebec—Canada, a Refined Neutral Approach - Valencia Giraldo, Marinela Del Carmen; Ricard, Simon; Anctil, François (Water, 2023)
There is currently much discussion as to whether probabilistic (top–down) or possibilistic (bottom–up) approaches are the most appropriate to estimate potential future climate impacts. In a context of deep uncertainty, such as future climate, bottom-up approaches aimed at assessing the sensitivity and vulnerability of systems to changes in climate variables have been gaining ground. A refined framework is proposed here (in terms of coherence, structure, uncertainty, and results analysis) that adopts the scenario–neutral method of the bottom–up approach, but also draws on some elements of the top–down approach. What better guides the task of assessing the potential hydroclimatological impacts of changing climatic conditions in terms of the sensitivity of the systems, differential analysis of climatic stressors, paths of change, and categorized response of the scenarios: past, changing, compensatory, and critical condition. The results revealed a regional behavior (of hydroclimatology, annual water balances, and snow) and a differential behavior (of low flows). We find, among others, the plausible scenario in which increases in temperature and precipitation would generate the same current mean annual flows, with a reduction of half of the snow, a decrease in low flows (significant, but differentiated between basins), and a generalized increase in dry events.

Field monitoring of river ice processes in the vicinity of ice control structures in the province of Quebec, Canada - Pourshahbaz, Hanif; Ghobrial, Tadros; Shakibaeinia, Ahmad (Canadian Journal of Civil Engineering, 2023)
Over the past decades, a variety of ice control structures (ICSs) have been designed and built, but to date, there has been no systematic evaluation of the effectiveness of these structures. To achieve this objective, first an understanding of the interaction between different ice processes and the ICSs must be established. For this purpose, a total of four ICSs located in the province of Québec were monitored during the 2021–2022 winter. The results showed that the ice jam holding time could vary from 1.5 to 68.5 h. The release of the jam was mechanically driven when the ratio of release to initiation Froude number was higher than one and was thermally driven when this ratio was lower than one, and the water temperature increased between initiation and release. Also, as the ratio of the total pier spacing to upstream river width increased, the holding time decreased.
Keywords: Ahmad_Shakibaeinia; Infolettre; Infolettre_Octobre_2023

Mechanisms of spring freshet generation in southern Quebec, Canada - Kinnard, Christophe; Nemri, Saida; Assani, Ali (2023)
Seasonal forecasting of spring floods in snow-covered basins is challenging due to the ambiguity in the driving processes, uncertain estimations of antecedent catchment conditions and the choice of predictor variables. In this study we attempt to improve the prediction of spring flow peaks in southern Quebec, Canada, by studying the preconditioning mechanisms of runoff generation and their impact on inter-annual variations in the timing and magnitude of spring peak flow. Historical observations and simulated data from a hydrological and snowmelt model were used to study the antecedent conditions that control flood characteristics in twelve snow-dominated catchments. Maximum snow accumulation (peak SWE), snowmelt and rainfall volume, snowmelt and rainfall intensity, and soil moisture were estimated during the pre-flood period. Stepwise multivariate linear regression analysis was used to identify the most relevant predictors and assess their relative contribution to the interannual variability of flood characteristics. Results show that interannual variations in spring peak flow are controlled differently between basins. Overall, interannual variations in peak flow were mainly governed, in order of importance, by snowmelt intensity, rainfall intensity, snowmelt volume, rainfall volume, peak SWE, and soil moisture. Variations in the timing of peak flow were controlled in most basins by rainfall volume and rainfall and snowmelt intensity. In the northernmost, snow-dominated basins, pre-flood rainfall amount and intensity mostly controlled peak flow variability, whereas in the southern, rainier basins snowpack conditions and melt dynamics controlled this variability. Snowpack interannual variations were found to be less important than variations in rainfall in forested basins, where snowmelt is more gradual. Conversely, peak flow was more sensitive to snowpack conditions in agricultural basins where snowmelt occurs faster. These results highlight the impact of land cover and use on spring flood generation mechanism, and the limited predictability potential of spring floods using simple methods and antecedent hydrological factors.
Keywords: Infolettre; Infolettre_Fevrier_2025; Kinnard_Christophe

Using the theory of planned behavior to identify key beliefs underlying flood-related adaptive behaviors in the province of Québec, Canada - Jacob, Johann; Valois, Pierre; Tessier, Maxime; Talbot, Denis; Anctil, François; Cloutier, Geneviève; Renaud, Jean-Sébastien (Journal of Flood Risk Management, 2023)
Given that flooding episodes are occurring at a greater rate due to climate change, individuals must adopt certain adaptation behaviors to prevent or mitigate the anticipated or negative impact of such events. However, few studies have assessed if and how households and individuals have actually taken action in this regard. Because some individual beliefs can be linked to facilitating factors and barriers to action, a better understanding of the adoption of adaptive behaviors requires a combined analysis of individual psychosocial factors. The purpose of this study was to develop a better understanding of the reasons underlying the adoption of behaviors related to structural adaptation to flooding by people living in or near flood-prone areas in the Province of Québec (Canada). Results of a series of structural equation modeling showed that behavioral, normative and control beliefs were all significant predictors of the respondents' intention to adopt structural flood protective behaviors, with normative beliefs being the strongest. By identifying the best psychosocial predictors of the adoption of such behaviors, the results of this study provide valuable insights regarding the most effective factors to be used in public health messages to promote the adoption of behaviors related to structural adaptation to flooding.
Keywords: Infolettre; Infolettre_Mai_2023

A comprehensive field investigation of the dynamic break-up processes on the Chaudière River, Quebec, Canada - Ghobrial, Tadros; Pelchat, Gabriel; Morse, Brian (Hydrology Research, 2023)
Abstract The Chaudière River in Quebec, Canada, is well known for its frequent ice jam flooding events. As part of a larger watershed research program, an extensive field campaign has been carried out during the 2018–2019 and 2019–2020 winter seasons to quantify the spatiotemporal characteristics of the break-up processes along the Chaudière River. The results showed that mid-winter ice jams have formed in the Intermediate Chaudière and persisted until spring break-up. Spring break-ups were initiated in the Upper Chaudière, and then, almost simultaneously, in the Intermediate and Lower Chaudière reaches. The break-up in the Intermediate Chaudière usually lasts longer than the rest of the river since the slope is much milder, and the occurrence of mid-winter ice jams has been seen to delay the ice clearing. A reach-by-reach characterization of the cumulative degree day of thawing and discharge thresholds for the onset of break-up has been identified. During the field campaign, 51 ice jams were documented together with their location, length, date of formation, and the morphological feature triggering jam formation. Break-up patterns, hydrometeorological thresholds of ice mobilization, and ice jam sites identified in this study can serve as a basis for the implementation of an early warning system.
Keywords: Infolettre; Infolettre_Septembre_2023

Climate change more than doubled the likelihood of extreme fire weather conditions in Eastern Canada - Barnes, C; Boulanger, Y; Keeping, T; Gachon, P; Gillett, N; Haas, O; Wang, X; Roberge, F; Kew, S; Heinrich, D; Singh, R; Vahlberg, M; et al. (2023)
Keywords: Gachon_Philippe

The new ‘surface storage’ concept versus the old ‘sponge effect’ concept: application to the analysis of the spatio-temporal variability of the annual daily maximum flow characteristics in southern Quebec (Canada) - Assani, Ali Arkamose; Zeroual, Ayoub; Kinnard, Christophe; Roy, Alexandre (Journal of Water and Climate Change, 2023)
Abstract This study confronts the new concept of ‘surface storage’ with the old concept of ‘sponge effect’ to explain the spatio-temporal variability of the annual daily maximum flows measured in 17 watersheds of southern Quebec during the period 1930–2019. The new concept takes into account the hydrological impacts of wetlands and other topographic components of the landscape (lakes, depressions, ditches, etc.) while that of the sponge effect only takes into account the hydrological impacts of wetlands. With regard to spatial variability, the area of wetlands and other water bodies is the variable best correlated negatively with the magnitude but positively with the duration of flows. As for the temporal variability, the application of the long-term trend tests revealed a significant increase in the magnitude and, to a lesser extent, the duration of the flows occurring in the watersheds of the north shore characterized by a greater area of wetlands and other water bodies (>5%). This increase is explained by the fact that the storage capacity of these land types, which remains unchanged over time, does not make it possible to store the surplus runoff water brought by the increase in rainfall during the snowmelt season.
Keywords: Infolettre; Infolettre_Septembre_2023; Kinnard_Christophe

Comparison of Spatio-Temporal Variability of Daily Maximum Flows in Cold-Season (Winter and Spring) in Southern Quebec (Canada) - Assani, Ali Arkamose (Hydrology, 2023)
Quebec has experienced a significant decrease in the amount of snow and an increase in temperature during the cold season. The objective of this study is to analyze the impacts of these climate changes on the spatio-temporal variability of the daily maximum flows generated by snowmelt in winter and spring using several statistical tests of correlation (spatial variability) and long-term trend (temporal variability). The study is based on the analysis of flows measured in 17 watersheds (1930–2019) grouped into three hydroclimatic regions. Regarding the spatial variability, the correlation analysis revealed that in winter, the flows are positively correlated with the agricultural area and the daily maximum winter temperature. In the spring, the flows are positively correlated with the drainage density and the snowfall but negatively correlated with the area of wetlands and the daily maximum spring temperature. As for temporal variability (long-term trend), the application of eight statistical tests revealed a generalized increase in flows in winter due to early snowmelt. In the spring, despite the decreased snow cover, no negative trend was observed due to the increase in the spring rainfall, which compensates for the decrease in the snowfall. This temporal evolution of flows in the spring does not correspond to the predictions of climate models. These predict a decrease in the magnitude of spring floods due to the decrease in the snowfall in southern Quebec.
Keywords: Infolettre; Infolettre_Avril_2023; Site_internet_RIISQ

Extreme Hydrological Drought in Southern Quebec (Canada): Natural and Anthropogenic Factors Interactions on its Spatio-Temporal Variability - Assani, Ali Arkamose (International Journal of Environmental Sciences & Natural Resources, 2023)

Fully integrating probabilistic flood forecasts into the decision-making process across southern Quebec, Canada: some factors to consider - Jean, Valérie; Boucher, Marie-Amélie; Frini, Anissa; Roussel, Dominic (Canadian Water Resources Journal / Revue canadienne des ressources hydriques, 2023)
Keywords: Infolettre; Infolettre_Septembre_2023